Protective and preferential import duties - Pigou, A. C. (London : Cass, 1968)
The book consists of two parts. The former deals broadly with the probable effects of moderate protective duties in a country such a England. The latter part of the book is devoted to a detailed examination of the policy of Preferential Tariffs between the mother country and her colonies
Bibliographical footnotes.
osc 13/07/2018
Loans
Keywords: Tariff; Import duties; Imperial preference